STUDI PENGARUH MEDIA ALTERNATIF UNTUK PERBANYAKAN PISANG BARANGAN (Musa acuminata L.) SECARA IN-VITRO - Rosmaina Rosmaina; Ragil Endika; Zulfahmi Zulfahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The main obstacles in the commercialization of seedlings mass propagation through tissue culture techniques is the high cost of the culture media component. therefore, the production of lowcost tissue culture is required. This study aims to develop low cost in-vitro media for the production of the seedlings of Barangan banana. The research was composed following Factorial Completely Randomized Design, the first factor was Terra Novalgro liquid fertilizer with three concentrations, namely 1, 2, and 3 ml L-1, while the second factor was Gandasil with 3 concentrations namely 1, 2, and 3 mg L-1, so obtained nine treatments, each treatment was repeated 10 times, so that there were 90 experimental units. MS media was used as control. The parameter observed was number of shoots, number of leaves and number of roots. The results of this study exhibited that the treatment of 1 ml L-1 liquid fertilizer + 2 mg L-1 foliar fertilizer produced 9.30 shoots/explant and 1.90 leaves/explant, that no significantly different from MS medium (control) which produced 9.0 shoots/explant and 0.3 leaves/explants. Therefore, the using completed liquid fertilizers and foliar fertilizers as medium in vitro propagation of barangan bananas can become an alternative replace MS medium, as well as reduced the cost of culture media as 91% -93% compared to MS media.